(untitled) (Security Dialogues, 2024)
The article deals with broadening the view of terrorist radicalization, starting from the causes that lead to terrorist radicalization, through social media as a friend of terrorist propaganda distribution, and up to the migration to the dark side of the Internet. The current global landscape is affected by multiple recent crises and largely with high uncertainty, this combined with overall hyper-connectivity is a fertile ground for terrorist radicalization. The impact that terrorists have is due to the spread of their narrative through the media, distributing propaganda material that is easily accessible to all. This material remains available and a potential risk for the spread of new recruits. The online environment is a key medium for terrorist propaganda where law enforcement agencies are forced to take deeper steps to deal with disinformation and propaganda spread by terrorist organizations, which in turn forces terrorists to change their structure and modus operandi.